2019
DOI: 10.1177/0032885519852079
|View full text |Cite
|
Sign up to set email alerts
|

Formerly Incarcerated Black Mothers Matter Too: Resisting Social Constructions of Motherhood

Abstract: Mass incarceration as a system of racialized and gendered social control has disproportionately impacted Black women, many of whom are mothers. Contrary to dominant social constructions of motherhood, these women employ their own strategies of mothering unique to their lived experiences. This study relies on interview data to understand Black women’s motherhood experiences post-incarceration. Drawing from five semistructured interviews of Black mothers across a large urban area in Texas, we argue for more crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
(52 reference statements)
1
17
0
Order By: Relevance
“…Centering the focus on mothers' primary motivations and experiences, rather than father involvement outcomes, contextualizes mediation processes and yields new understandings regarding what it means to be a "good mother." For example, our findings are parallel to motherwork research studies (Gurusami, 2019;Mitchell & Davis, 2019) that examine the lived experience of previously incarcerated mothers. Motherwork in these studies is characterized by "hypervigilance," which is centered on children's safety and combating stigma.…”
Section: Discussionsupporting
confidence: 71%
“…Centering the focus on mothers' primary motivations and experiences, rather than father involvement outcomes, contextualizes mediation processes and yields new understandings regarding what it means to be a "good mother." For example, our findings are parallel to motherwork research studies (Gurusami, 2019;Mitchell & Davis, 2019) that examine the lived experience of previously incarcerated mothers. Motherwork in these studies is characterized by "hypervigilance," which is centered on children's safety and combating stigma.…”
Section: Discussionsupporting
confidence: 71%
“…As shown in this study, their experiences are viciously raced and gendered—and often ultimately attached to deep family roots that go back to tradition. Also, missing within much of the literature is the extent to which formerly incarcerated Black women’s lived realities are inevitably passed down to their children (e.g., Mitchell & Davis, 2019). As historical materialism explains, ideological trickery within social institutions, designed to both help and destroy, is to blame for Black women’s continual suffering and displacement in US society.…”
Section: Discussionmentioning
confidence: 99%
“…Raising children while being a formerly incarcerated Black woman can be extremely challenging given the reality that Black women often do not receive childcare assistance from their partners or their children's fathers (Doge & Pogrebin, 2001). In addition, research has found that Black women, especially ones from "ghettoized communities," have to navigate their returns to society worrying about their children's wellbeing, housing, and education while dealing with substance abuse and mental health issues (Mitchell & Davis, 2019). Thus, their return to society is nuanced and unique.…”
Section: Incarcerated Black Women and Mothersmentioning
confidence: 99%
“…Through a critical race feminist lens, scholarly research has made important contributions in areas focused on incarcerated mothers, mothers of incarcerated children, and adolescent girls of incarcerated parents (Garcia-Hallett, 2019;Hayes-Bautista, 2013;Lopez & Corona, 2012;Mitchell & Davis, 2019). Yet, little attention has been given to how parental incarceration specifically intersects with race, ethnicity, and gender for young women.…”
Section: The Process Of Parental Incarcerationmentioning
confidence: 99%
“…Further, research depicting the challenges of mass incarceration in the lives of young Black and Latinx women has even more rarity. In fact, scholars assert that the narratives of Black and Latinx women are lacking in criminology research and dismisses the intersectional framework of race, gender, and incarceration (Christian & Thomas, 2009;Mitchell & Davis, 2019).…”
Section: Introductionmentioning
confidence: 99%